Cost-Effectiveness Analysis Of The Medical Check-Up Program In Early Detection Of Non-Communicable Diseases (NCDs) At The Main Clinic Of The DPR RI - Entin Sumartini; Dewi Purnamawati (CV. AFDIFAL MAJU BERKAH, 2026)
The DPR RI Main Clinic organizes a Medical Check-Up (MCU) program for employees of the Secretariat General (Setjen) of the DPR RI as an effort to early detect non-communicable diseases (PTM). DEDICATION 2024 Program data (n=1,063) showed a very high prevalence of NCDs: 89.6% of participants had at least one clinical disorder, with a predominance of central obesity (69.0%), hypertension (60.7%), and dyslipidemia (52.6%). Even though the MCU program budget ranges from IDR 1.3 million to IDR 2.5 million per participant, there has never been a formal economic study that calculates the cost efficiency per case of NCDs detected. Analyze the cost-effectiveness of the MCU program in early detection of NCDs at the DPR RI Main Clinic, including calculating the Average Cost-Effectiveness Ratio (ACER), Incremental Cost-Effectiveness Ratio (ICER), and Return on Investment (ROI) in preventing NCDs for four MCU package scenarios (Plan I–IV). Research using mixed methods approach with sequential explanatory design. The quantitative component is descriptive-analytic retrospective based on secondary data from MCU echelon II–IV medical records (n=208, total sampling), 2024 DEDICATION data (n=1,063), and 2022–2024 clinic financial reports. Unit cost calculations use the Activity-Based Costing (ABC) method. The qualitative component uses semi-structured in-depth interviews with 9 key informants based on Edward III's (1980) policy implementation framework. This research will produce ACER, ICER, and ROI values ​​for the four MCU scenarios, as well as identify the implementation factors that have the most influence on program efficiency. Projections of budget requirements for the expansion of the MCU to 2,786 active employees of the Secretariat General of the DPR RI will also be produced based on an economics of scale analysis. Expected The MCU Main Clinic Program of the DPR RI is hypothesized to be cost-effective with an ACER value below the WHO willingness-to-pay (WTP) threshold of 1× Indonesia's GDP per capita (Rp. 66 million/case). Scenarios with greater participant coverage are predicted to produce lower ACER due to the economies of scale effect. The results of the research will be the basis for recommendations for MCU policies that are efficient, high quality and fair for all employees of the Secretariat General of the DPR RI.